Ultrafast LC-MS/MS analysis of 5-hydroxyindoleacetic acid (5-HIAA) in serum - Oxelbark, Joakim; Lövenhamn, Annicka (Scandinavian journal of clinical and laboratory investigation, 2021)
A very quick and easy LC-MS/MS analysis method for 5-HIAA (5-hydoxyindoleacetic acid) has been developed. The method was fully validated and proved to work well in a clinical setting. Precision at the upper reference limit 123 nmol/L was 3,3% CV. Accuracy ranged from 96% at low levels (50-100 nmol/L) to 99.7% at high levels (500 nmol/L). A previously reported reference interval of 35-123 nmol/L was confirmed as valid based on analysis of 40 samples from voluntary blood donors.